Practical Stability for Conformable Time-Delay Systems - Maher Kharrat; Hamdi Gassara; Mohamed Rhaima; Lassaad Mchiri; A. Ben Makhlouf (Discrete Dynamics in Nature and Society)
This article investigates the practical exponential stability and design problems of conformable time-delay systems. Sufficient conditions that confirm the practical exponential stability and design of the proposed class of systems are given by utilizing an adequate Lyapunov–Krasovskii functional (L-KF). These conditions are expressed in the form of linear matrix inequalities (LMI) which could be solved by using solvers in LMI Toolbox of MATLAB. Two numerical examples are given to illustrate the applicability of the proposed results.